2018
DOI: 10.3389/fevo.2018.00168
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Shifts in the Number of Axons in the Olfactory Tract and Optic Nerve in Two Species of Deep-Sea Grenadier Fish (Gadiformes: Macrouridae: Coryphaenoides)

Abstract: Neuroanatomical studies of the peripheral sense organs and brains of deep-sea fishes are particularly useful for predicting their sensory capabilities and ultimately their behavior. Over the abyssal plane (between 2,000 and 6,000 m), communities of grenadiers (Gadiformes: Macrouridae) play an important ecological role as predator-scavengers. Previous studies suggest that these fishes rely heavily on chemosensation, especially olfaction. Furthermore, at least one species, Coryphaenoides armatus, undergoes an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
(138 reference statements)
0
10
0
Order By: Relevance
“…Similar work is required in other taxa, including fishes, for which ontogenetic shifts in relative OB size have been documented [Lisney et al, 2007[Lisney et al, , 2017. A recent study by Lisney et al [2018] showed that the total number of axons (UM and M pooled) in the OT of two deep-sea fish (Coryphaenoides armatus and Coryphaenoides profundicolus) increased with ontogeny. This study reveals that the number of secondary inputs increases with ontogeny and predicts a relative shift in OB size [Lisney and Collin, 2006;Lisney et al, 2007].…”
Section: Developmental Effects On Convergence Ratiosmentioning
confidence: 72%
“…Similar work is required in other taxa, including fishes, for which ontogenetic shifts in relative OB size have been documented [Lisney et al, 2007[Lisney et al, , 2017. A recent study by Lisney et al [2018] showed that the total number of axons (UM and M pooled) in the OT of two deep-sea fish (Coryphaenoides armatus and Coryphaenoides profundicolus) increased with ontogeny. This study reveals that the number of secondary inputs increases with ontogeny and predicts a relative shift in OB size [Lisney and Collin, 2006;Lisney et al, 2007].…”
Section: Developmental Effects On Convergence Ratiosmentioning
confidence: 72%
“…In mammals, postnatal brain growth is attributed to development and increase of fibers, as also demonstrated in fishes [Huber and Rylander, 1992], as well as glial elements [Iaskin, 2011]. Furthermore, changes in brain growth may also be attributed to the emergence of new synapses [Gheusi et al, 2000] as well as increased myelination of established synapses [Lisney et al, 2018]. As research in these additional factors in elasmobranchs is scarce [Yopak et al, 2014], future studies should quantify rates of neurogenesis and synaptogenesis in sharks to more completely understand the elements contributing to brain growth.…”
Section: Ontogenetic Changes In Brain Sizementioning
confidence: 93%
“…In the abyssal grenadier (C. armatus), smaller individuals use their rostrum to dig in muddy substrate to find benthic invertebrates and possess a relatively enlarged optic tectum and relatively reduced olfactory bulbs; larger individuals swim above the bottom to detect their prey and exhibit the converse pattern, with a relatively reduced optic tectum and relatively enlarged olfactory bulbs [Wagner, 2003]. These ontogenetic shifts are not restricted to size of brain regions, but are also reflected in optic nerve and olfactory tract axon numbers in some species [Lisney et al, 2018]. Additionally, many larval fish are planktivorous, while adults shift to a benthic feeding style [Wanzenböck and Schierner, 1989]; this shift in habitat and feeding mode is similarly marked by a relative decrease in optic tectum size [Fuiman, 1988;Kotrschal, 1989, 1990;Kotrschal et al, 1990;Montgomery and Sutherland, 1997].…”
Section: Ontogenetic Changes In Brain Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased acuity in chemosensory abilities such as olfaction and taste as compensation for loss of vision was reported in cave fishes [23,24], whereas acceleration of OR gene loss was shown to coincide with the acquisition of acute vision in haplorhines [11]. In addition, two species of deep-sea grenadier fishes living between 2000 and 6000 m depth were reported to have undergone an ontogenetic shift in sensory orientation, with olfaction being more important than vision in large individuals [25]. Therefore, it is of great interest to examine how environmental adaptations reshape the hierarchical structure of the olfactory receptor repertoires in deep-living fishes.…”
Section: Introductionmentioning
confidence: 99%